Lively Social Space, Well-Being Activity, and Urban Design: Findings From a Low-Cost Community-Led Public Space Intervention. (July 2017) - Anderson, Jamie; Ruggeri, Kai; Steemers, Koen; Huppert, Felicia
Empirical urban design research emphasizes the support in vitality of public space use. We examine the extent to which a public space intervention promoted liveliness and three key behaviors that enhance well-being ("connect, " "be active, " and "take notice"). The exploratory study combined directly observed behaviors with self-reported, before and after community-led physical improvements to a public space in central Manchester (the United Kingdom). Observation data ( n = 22, 956) and surveys (subsample = 212) were collected over two 3-week periods. The intervention brought significant and substantial increases in liveliness of the space and well-being activities. None of these activities showed increases in a control space during the same periods. The findings demonstrate the feasibility of the research methods, and the impact of improved quality of outdoor neighborhood space on liveliness and well-being activities. The local community also played a key role in conceiving of and delivering an effective and affordable intervention. The findings have implications for researchers, policy makers, and communities alike.